One-Step Synthesis of Fluorescent Boron Nitride Quantum Dots via a Hydrothermal Strategy Using Melamine as Nitrogen Source for the Detection of Ferric Ions - Huo, Bingbing (Langmuir : the ACS journal of surfaces and colloids, 2017)
A facile and effective approach for the preparation of functionalized born nitride quantum dots (BNQDs) with blue fluorescence was explored by the hydrothermal treatment of the mixture of boric acid and melamine at 200 °C for 15 h. The as-prepared BNQDs were characterized by transmission electron microscopy (TEM), high-resolution TEM, atomic force microscopy, X-ray photoelectron spectroscopy, UV-vis spectroscopy, and fluorescence spectroscopy. The single layered BNQDs with the average size of 3 nm showed a blue light emission under the illumination of the UV light. The BNQDs could be easily dispersed in an aqueous medium and applied as fluorescent probes for selective detection of Fe3+ with remarkable selectivity and sensitivity (the lowest detection limit was 0.3 μM). The fluorescence fiber imaging demonstrated that the as-prepared quantum dots could be used as a valuable fluorchrome. Therefore, the BNQDs could be envisioned for potential applications in many fields such as biocompatible staining, fluorescent probes, and biological labeling